Structural organisation of the emotional component of rigidity - Pevneva, Anzhela N. (Journal of the Belarusian State University. Philosophy and Psychology, 2024)
The emotional component of rigidity is considered based on the concept of mental rigidity developed by G. V. Zalevsky. The ideas about the nature of mental rigidity of the individual have been expanded, in particular, the structural organisation of its emotional component has been determined. The sample population (n = 667) is presented, diagnostic methods and statistical data processing are described, and the results of the study are analysed. It has been suggested that there is a bipolar structural organisation of the emotional component of rigidity, including leading and basic subcomponents that are consistent with each other, measured using appropriate questionnaires, with poles split into subregions. The subcomponents of the pole of affective rigidity (sensitive rigidity, rigidity as a state and rigidity-1 (H. Eysenck)) and the poles of cognitive flexibility (alternative, control and rigidity-2 (L. N. Sobchik)) with the leading subcomponents (sensitive rigidity at one pole and alternative at the other pole). The discovery of positive and negative extra- and intra-connections of the subcomponents of the emotional component of rigidity with psychological manifestations close to them in content, related to the emotional sphere, as well as to other spheres of a person’s life, contributed to the establishment of the phenomenon of splitting of the bipolar poles of affective rigidity and cognitive flexibility in the subarea. The findings add to the conceptual model of rigidity.